Dynamic Characteristic Analysis of Two-stage Planetary Gear with Broken Tooth Fault based on ADAMS - Liu Xiaole; Liu Houguang; Cheng Gang; Xu Dan (Jixie chuandong)
Taking two-stage planetary gear of the cutting part of MG900 /2215-GWD shearer as study object,the dynamics analysis simulation of it is carried out by using virtual prototype technology.By comparing the meshing force curves in time domain and frequency domain of the health and several broken tooth fault of varying degrees,the dynamic response of two-stage planetary gear system under fault condition is analyzed.It can be found that under fault condition,the mesh force side bands of energy become intensive,and the intensity increases with the extent of the damage increase.The research results can provide a theoretical basis for two-stage planetary gear fault diagnosis and testing.